Program Pendampingan Masyarakat Tani Melalui Pembuatan Pupuk Kompos Padat Dari Limbah Kotoran Sapi Dengan Metoda Fermentasi Menggunakan EM4 di Paok Lombok Kabupaten Lombok Timur NusaTenggara Barat: (Farming Community Assistance Program by Making Solid Compost Fertilizer from Cow Manure Using the Fermentation Method Using EM4 in Paok Lombok, East Lombok Regency, West Nusa Tenggara) - Ahmad Fadli; R. Didi Kuswara; Zulkarnain Gazali; Siti Wardatul Jannah; Maya Ekaningtias Maya; Nening Listari; Nurmiati; Reni Andriani; Samiin Hadi Harianto (AL HAYAT: Jurnal Pengabdian Masyarakat, 2024)
Activities for the community were carried out by the Biology Education Study Program PkM team together with students in Paok Hamlet, East Lombok, Paok Lombok Village, Suralaga District, East Lombok Regency, West Nusa Tenggara through counseling and training for farmer groups on how to make compost fertilizer from cow dung waste. The objectives of this activity include; first, provide understanding and skills to farmers to maximize the use of organic fertilizers rather than chemical fertilizers, second, provide skills to local communities on how to make compost from cow dung waste and third, help local communities to increase crop yields and income from the agricultural sector. The method used in this community service is the method of socialization, discussion and training on how to use cow dung as an ingredient in making compost fertilizer. During the activity process, the participants were quite enthusiastic about taking part in the training, this was also because many local people did not know and understand that cow dung could be processed into compost which was environmentally friendly and able to increase their agricultural yields. In general, the results obtained in this service activity are that participants have initial knowledge, understanding and skills regarding the use of cow dung as compost fertilizer which is very useful for increasing agricultural yields. Apart from that, of course service participants are able to make compost from cow dung waste and how to apply it to plants. During the activity, a limited amount of compost was produced as an example for the participants and a reference for them to make compost again.